2022
DOI: 10.3389/fpls.2022.866409
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-Priming Mediated Cellular Networks for Abiotic Stress Management in Plants

Abstract: Plants can adapt to different environmental conditions and can survive even under very harsh conditions. They have developed elaborate networks of receptors and signaling components, which modulate their biochemistry and physiology by regulating the genetic information. Plants also have the abilities to transmit information between their different parts to ensure a holistic response to any adverse environmental challenge. One such phenomenon that has received greater attention in recent years is called stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 383 publications
(399 reference statements)
0
10
0
Order By: Relevance
“…Our network analysis further identified two HSF transcription factors (HSFA4A, HSFA8) associated with the SA signalling pathway that are up-regulated in AT1703 in response to S. sclerotiorum. While HSFs have been shown to interact directly with EDS1, resulting in SA accumulation in response to pathogen attack 47,48 , similarly to TGA10, HSFA4A and HSFA8 have specifically been implicated in the host ROS response as well as activation of the host antioxidant system 49,50 . Activation of these HSFs can act through phosphorylation by MPK3 in response to stress, which also demonstrates significant up-regulation in AT1703 A. thaliana in response to S. sclerotiorum 49,51,52 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our network analysis further identified two HSF transcription factors (HSFA4A, HSFA8) associated with the SA signalling pathway that are up-regulated in AT1703 in response to S. sclerotiorum. While HSFs have been shown to interact directly with EDS1, resulting in SA accumulation in response to pathogen attack 47,48 , similarly to TGA10, HSFA4A and HSFA8 have specifically been implicated in the host ROS response as well as activation of the host antioxidant system 49,50 . Activation of these HSFs can act through phosphorylation by MPK3 in response to stress, which also demonstrates significant up-regulation in AT1703 A. thaliana in response to S. sclerotiorum 49,51,52 .…”
Section: Discussionmentioning
confidence: 99%
“…While HSFs have been shown to interact directly with EDS1, resulting in SA accumulation in response to pathogen attack 47,48 , similarly to TGA10, HSFA4A and HSFA8 have specifically been implicated in the host ROS response as well as activation of the host antioxidant system 49,50 . Activation of these HSFs can act through phosphorylation by MPK3 in response to stress, which also demonstrates significant up-regulation in AT1703 A. thaliana in response to S. sclerotiorum 49,51,52 . While these data suggest SAR activity is an essential component of a successful defense response against S. sclerotiorum infection, SAR alone is insufficient to protect the host, as quantitative disease resistance is complex and requires the coordination of multiple defense pathways and processes 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, pre-exposure to mild heat stress can mitigate heat damage while preparing the organism for more severe, potentially lethal stress, a phenomenon known as priming or acquired stress resistance (19)(20)(21)(22). This general mechanism, which is well known in plants, is also widespread in microorganisms, helping them cope with changing conditions (21,(23)(24)(25)(26)(27). Studies in budding yeast showed that priming is dependent on nascent protein synthesis during moderate but not severe heat stress (18,20).…”
Section: Introductionmentioning
confidence: 99%
“…Priming (also known as memory) is an adaptation strategy to gain tolerance against more severe stress conditions through the memorized effect induced by moderate stress for plastic growth and development of plants under unfavorable conditions [ 10 , 11 ]. In nature, mild stress can be manifested through various environmental fluctuations, such as dynamic and cyclic changes in temperature, water availability, and nutrient limitation [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In nature, mild stress can be manifested through various environmental fluctuations, such as dynamic and cyclic changes in temperature, water availability, and nutrient limitation [ 10 ]. The stress adaptation process by priming has been proposed to occur through the pre-accumulation of stress-responsive transcripts, the alteration in levels of key metabolites, and the accumulation and phosphorylation of stress mitogen-activated protein kinases (MPKs) and epigenetic regulation [ 10 , 11 ]. In other words, showing a priming effect can be speculated as a weak-stress state in plants.…”
Section: Introductionmentioning
confidence: 99%